Strategi Bank Btn Syariah Dalam Penyelesaian Sengketa Kpr (Kredit Pemilikan Rumah) Bermasalah(Studi Kasus Bank BTN Syariah Surakarta) - Asyrifah, Zulfa Naili, Mutimatun Ni'ami, S.H., M.Hum (2016)
Talking about the mortgage, in this case can not be separated from the role of the State Savings Bank (BTN). The Bank has long focused on services and products to the community in terms of providing mortgages, but it also opened the same service on the BTN Syariah with its superior product that Sharia mortgages. Loan Growth (KPR) Islamic State Savings Bank for the financing of citizens who want to get home fast enough lately. Of the five branches BTN has a division of sharia, for funds for homeownership managed sharia continues to expand, even beyond the development of conventional banks in granting credit facilities contained in a credit agreement by banks to borrowers is not without risk, because the risk of possible especially because the debtor is not required to pay its debts in full or in cash, but the debtor was given credence by the Act in the credit agreement to pay later gradually or in installments. Risk is generally the case is a failure or congestion in the settlement of loans (credit risk). Such risks are generally detrimental to the creditors need to be carefully considered by the bank as creditor, so that in the process of bank lending the necessary confidence on capability and capacity of the debtor to pay its debts as well as observing the principles of healthy bank lending.